Measuring and modelling internet diffusion using second level domains: The case of Italy - Andrea Bonaccorsi; Maurizio Martinelli; Cristina Rossi; Irma Serrecchia (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2002)
The last 10 years witnessed an exponential growth of the Internet. According to Hobbes' Internet Timeline, the Internet hosts are about 93 million, while in 1989 they were 100,000. The same happens for second level domain names. In July 1989 the registered domains were about 3,900 while they were over 2 million in July 2000. This paper reports about the construction of a database containing daily observations on registrations of second level domain names underneath the it ccTLD in order to analyse the diffusion of Internet among families and businesses. The section of the database referring to domains registered by individuals is analysed. The penetration rate over the relevant population of potential adopters is computed at highly disaggregated geographical level (province). A concentration analysis is carried out to investigate whether the geographical distribution of Internet is less concentrated than population and income suggesting a diffusive effect. Regression analysis is carried out using demographic, social, economic and infrastructure indicators. Finally we briefly describe the further developments of our research. At the present we are constructing a database containing domains registered by firms together with data about the registrants; the idea is to use this new database and the previous one in order to check for the existence of power laws both in the number of domains registered in each province and in the number of domains registered by each firm.
Keywords: 330; Domain names; Internet metrics; Diffusion; Power laws; Zipf's law; Internet; Innovationsdiffusion; Innovationsdiffusion; Messung; Italien